Drop coating deposition Raman spectroscopy of liposomes: role of cholesterol - Kočišová, Eva; Antalík, Andrej; Procházka, Marek (Chemistry and physics of lipids, 2013)
Drop coating deposition Raman (DCDR) spectroscopy was used to study liposomes (DPPC and asolectin) with growing proportion of cholesterol. Deposited samples of both liposomes on special hydrophobic surface formed a dried drop with a circular shape with a ring of concentrated liposomes at the outer edge. The presence of cholesterol in liposome causes a diminishing of the drop size and an increasing in diameter of the ring, but DPPC with 20% of cholesterol forms the compact drop without the ring. Raman spectra contain characteristics of both lipids and cholesterol, liposomes do not change their initial phase state after drying. Spectral mapping shows that maximum Raman intensity originated from the inner part of the ring. Our results suggest that DCDR spectroscopy can be used for studying lipids containing cholesterol in situ.
Keywords: hydrofobní a hydrofilní interakce; Liposome; Hydrophobic and Hydrophilic Interactions; DPPC; Phosphatidylcholines; 1,2-dipalmitoylfosfatidylcholin; liposomy; Liposomes; Spectrum Analysis, Raman; 1,2-Dipalmitoylphosphatidylcholine; fosfatidylcholiny; Cholesterol; Drop coating deposition Raman spectroscopy; Asolectin; Ramanova spektroskopie; cholesterol